Transmission, serologic and tissue responses in chickens vaccinated with Mycoplasma gallisepticum F strain (MG-F) - Machado,Leandro S. (2016)
Abstract: MG-F protects chickens from MG Mycoplasmosis and monitoring is done by serology (SAR and ELISA) and PCR. Histopathology is used to evaluate bird response to MG. This study evaluated MG-F profile vaccination in SPF chicken. This trial used 100 chickens, being 40 unvaccinated (G1), 40 eye-drop vaccinated at 8 weeks of age with MG-F ( Ceva Animal Health , São Paulo , SP , Brazil ) (G2) and 20 immunized by contact (G3) . Samples were obtained on the 8th, 12th, 15th, 18th, 20th and 24th week for SAR, ELISA and PCR. Fragments of trachea and air sac, for microscopy, were got after necropsies on the 15th and 24th week. Up to 12 weeks there was no significant difference among groups by SAR. SAR reactions appeared from the 15th week with these averages: G1 (1.7, 1.76 , 0.1, 0.15) , G2 (7.81, 7.65, 8.25, 6.29) and G3 (8.1, 8.5, 9.5, 6.16), while by ELISA it occurred after the 18th week with optical densities averages: G1 (0.19, 0.14, 0.16) , G2 (0.47, 0.45, 0.41) and G3 (0.55, 0.51, 0.51) . Positivity in G3 by PCR occurred seven weeks after exposure. At the 15th week the air sac score means were 0.20, 0.55, and 0.32 and 24th week were 0.15, 0.80 and 0.66 (p>0.05). For trachea, G2 (0.48) yielded higher score average than G1 (0.10) and G3 (0.00) on the 15th week. Changes in G3 were seen only at 24th week, being this average (1.00) significantly different (p<0,05) from G1 (0.08) and G2 (0.46). SAR and PCR detected MG-F in G3 earlier than ELISA. Higher tracheal changes for G2 and G3 as compared to G1 could be ascribed to MG-F vaccine infection.